Pengaruh Sistem Pengendalian Internal, Komitmen Organisasi, dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan dengan Kompetensi Sumber Daya Manusa Sebagai Variabel Moderasi - Harpidalinda, Sopia; Muhsin, Muhsin; Rusliyawati, Rusliyawati; Karpriana, Angga Permadi (Papanda Publisher, 2024)
The purpose of this research is to determine the influence of internal control systems, organizational commitment, and the use of information technology on the quality of financial reports with human resource competency as moderation. This research uses quantitative methods and uses primary data. Determination of the sample size in this study used a saturated sample. The population in this study was 35 employees, so the sample used was 35 employees. WarpPLS 7.0 tool is used for data analysis. The research results show that the independent variables (internal control system, organizational commitment, use of information technology) are able to influence financial quality, while the moderating variable (human resource competency) is not strong enough to strengthen the relationship between the independent variable and the dependent variable. Keyword: Internal Control System, Organizational Commitment, Use Of Information Technology